Survey on channel assignment algorithms using partially overlapped channels in wireless Mesh network - Ji-hong WANG; Wen-xiao SHI; Yu-xin LI; Feng JIN; Chun-yue WANG (Tongxin xuebao)
Capacity degradation caused by co-channel interference was a major challenge faced by wireless Mesh net-work. Partially overlapped channels could be carefully utilized to reduce or even eliminate co-channel interference. The basic concept of partially overlapped channels was presented, and then current partially overlapped channel assignment algorithms both at home and abroad were classified, summarized and analyzed from unicast and multicast point of view;problems and challenges of partially overlapped channel assignment were deeply analyzed, and the future directions for partially overlapped channels were pointed out. Partially overlapped channels are expected to help wireless Mesh net-works move towards the ideal solution for last mile access further.